Plant Species Diversity of Pangi Binangga Nature Reserve, Central Sulawesi - Muhammad F. R. M. Saleh; Alex Hartana (Media Konservasi, 2017)
Pangi Binangga Nature Reserve is one of eight nature reserves in Central Sulawesi. In 1998, Pangi Binangga was designated as a conservation area, however, the diversty of the plant species not been recognized and reported. Pangi Binangga Nature Reserve is a lowland forest with vegetation and grassland forest, with primary and secondary forest vegetation. The objectives of this research are to provide informations of plant species in the Pangi Binangga Area. Exploration method was conducted throughout the region, and found 518 species. Rubiaceae, Euphorbiaceae, Moraceae, Compositae, Araceae, Urticaceae dominate in Pangi Binangga forest. Four species of them are endemic to Sulawesi, five species belong to endangered plants and 10 species of invasive. Keywords: biodiversity, endemic, invasive, Sulawesi